19th International Congress of Metrology (CIM2019) 2019
DOI: 10.1051/metrology/201907001
|View full text |Cite
|
Sign up to set email alerts
|

Metrological references for health care based on entropy

Abstract: Consistent diagnosis in healthcare relies, in part, on quality assurance of categorical observations, such as responses to ability tests and patient surveys. Linking classifications on such nominal and ordinal scales to decision-making involves a combination of logit transformations and novel entropy-based estimates of measurement information throughout the measurement process. This paper presents how entropy can explain and predict entity attributes (such as task difficulty), instrument ability and resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Our understanding means that memory task difficulty could be sufficiently explained and captured by mathematically formulating CSEs where entropy is shown to be the dominant explanatory variable. Strikingly, for the memory tests CBT and DST, as well as in our previous work on KCT [8,12,43], it is found that essentially the same CSE describes task difficulty within uncertainties for all these non-verbal sequence tests, with basically just one explanatory variable, namely Entropy. These results contrast with the conclusions of several previous studies, e.g., [10,41,42,45] where more than one explanatory variable was claimed to be significant, while at the same time not explicitly declaring measurement uncertainties nor using the Rasch model.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Our understanding means that memory task difficulty could be sufficiently explained and captured by mathematically formulating CSEs where entropy is shown to be the dominant explanatory variable. Strikingly, for the memory tests CBT and DST, as well as in our previous work on KCT [8,12,43], it is found that essentially the same CSE describes task difficulty within uncertainties for all these non-verbal sequence tests, with basically just one explanatory variable, namely Entropy. These results contrast with the conclusions of several previous studies, e.g., [10,41,42,45] where more than one explanatory variable was claimed to be significant, while at the same time not explicitly declaring measurement uncertainties nor using the Rasch model.…”
Section: Discussionsupporting
confidence: 56%
“…Continuing our presentation of entropy and memory task difficulty, the CBT and DST (and the Knox Cube Test (KCT), as shown in our earlier work [8,12,43], and other memory sequence tests) can be characterized in general in terms of a message in which a number, G , which can be summed to unity. The total number, P, of messages that can be obtained by distributing the symbols at random over the G cells (with never more than one symbol per cell) is P = G!…”
Section: Entropy and Construct Specification Equationsmentioning
confidence: 76%
See 3 more Smart Citations